2011
DOI: 10.1590/s0100-736x2011000900002
|View full text |Cite
|
Sign up to set email alerts
|

Weak phenotypic reversion of ivermectin resistance in a field resistant isolate of Haemonchus contortus by verapamil

Abstract: Recent advances in anthelmintic resistant phenotype reversion by Pgp modulating drugs in ruminant nematodes indicate that this can be a useful tool to helminth control. The aim of the present study was to evaluate the efficacy of ivermectin (IVM) in combination with verapamil (VRP), in oil or water-based vehicle, against an IVM-resistant field isolate of Haemonchus contortus through a larval migration assay and experimental infection trial. In the in vitro assay was observed a phenotypic reversion of H. contor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Our results showed that OFIEOH plus IVM increased L3 inhibition by 1.5 times. A synergistic effect was also observed by reference [ 22 ] when using IVM in combination with verapamil, a calcium channel blocker, with LMT and [ 45 ] in vivo, against H. contortus naturally infected sheep. The effect of the combination of phenolic compounds and/or flavonoids with commercial drugs to control gastrointestinal parasites of livestock still has to be extensively tested to secure maximum animal safety.…”
Section: Resultssupporting
confidence: 62%
“…Our results showed that OFIEOH plus IVM increased L3 inhibition by 1.5 times. A synergistic effect was also observed by reference [ 22 ] when using IVM in combination with verapamil, a calcium channel blocker, with LMT and [ 45 ] in vivo, against H. contortus naturally infected sheep. The effect of the combination of phenolic compounds and/or flavonoids with commercial drugs to control gastrointestinal parasites of livestock still has to be extensively tested to secure maximum animal safety.…”
Section: Resultssupporting
confidence: 62%
“…Abomasums were individually subjected to digestion with a pepsin hydrochloric acid solution (Wood et al 1995). The contents of each segment were fixed in 70.0% alcohol (Borges et al 2011). Remaining organs were also inspected for the presence of possible helminth species (Wood et al, 1995).…”
Section: Fecal Collection Parasitological Necropsies and Helminth Spmentioning
confidence: 99%
“…For example, in triclabendazole resistant Fasciola hepatica the roles of flavin monooxygenases and cytochromes P450 were proved using the inhibitors methimazole ( Devine et al, 2009 ) and piperonyl butoxide ( Devine et al, 2011 ), respectively. Verapamil, a well-known inhibitor of efflux transporters P-glycoproteins (Pgp), reversed the resistance to ivermectin in Fasciola hepatica ( Savage et al, 2013 ) and H. contortus ( Borges et al, 2011 ). The UGT inhibitors 5-NU, DNP and SP have often been used in various organisms to demonstrate the role of UGTs in resistance.…”
Section: Discussionmentioning
confidence: 99%